A Comprehensive Management of Dushta Vrana Vis-A-Vis Diabetic Ulcer - A Case Study (International Journal of Ayurveda and Pharma Research, 2023)
Vrana is a clinical condition which occupies the area of skin and remains till body survives. Dushta Vrana is the Vrana having the features of Durgandha (bad smell), Pooyayukta (pus filled), Utsangi (elevated), Chirakali (chronic), Dooshita (afflicted by Tridosha vitiation), Atigandha Varna Srava (discharge with excessive odour and coloured), Vedanayukta (painful) and opposite to Shuddha Vrana (healing wound). Diabetic foot ulcer global prevalence is 6.3% with male predominancy and higher in type 2 diabetic patients (6.4%) than in type 1 diabetics (5.5%).In this report, a 70-year-old who was diagnosed with chronic non-healing diabetic wound treated with comprehensive Ayurvedic medicines based on the observations made on the nature of the wound. The main cause for the wound was uncontrolled type 2 diabetes mellitus, which was managed with both Ayurveda and conventional drugs. Patient gradually showed improvement. Total healing required 6 months.